The Effectiveness of the Two Stay Two Stray Model using Pocket Number Media in Social Sciences Subjects - Risti, Ovibella; Haryani, Sri; Handoyo, Eko (Journal of Primary Education)
The purpose of this study was to determine the effectiveness of the Two Stay Two Stray (TSTS) learning model using Number Pocket media on social studies subjects in grade IV Public Elementary School 01 Adipala, Cilacap. The method in this study was an experimental method with a sample of grade IV A as an experimental class and grade IV B as a control class. The sampling technique was applied in this study is research design was used pre-test – post-test control group design. The data collection techniques to determine the increased in the interest using the student learning interest is questionnaires, whereas, to measure the achievement of students using evaluation questions (pre-test – post-test). Based on the results of the hypothesis test, interest data and student achievement showed that 2.805 > 2.06, therefore, it can be said that there are differences in the interest and learning achievement between the control class and the experimental class. Based on the results of the student learning interest data showed that the significance value (0.000 < 0.05). Meanwhile, the results of the student achievement test hypothesis showed that the significance value (0.000 < 0.05). Based on these data, it can be concluded that the application of the TSTS model assisted with Number Pocket media is more effective on students' interest and learning achievement in social studies subjects in grade IV.